2009
DOI: 10.1093/hmg/ddp533
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Rpgr is required for normal retinal development and plays a role in dynein-based retrograde transport processes

Abstract: Mutations in the human RPGR gene cause one of the most common and severe forms of inherited retinal dystrophy, but the function of its protein product remains unclear. We have identified two genes resembling human RPGR (ZFRPGR1, ZFRPGR2) in zebrafish (Danio rerio), both of which are expressed within the nascent and adult eye as well as more widely during development. ZFRPGR2 appears to be functionally orthologous to human RPGR, because it encodes similar protein isoforms (ZFRPGR2(ORF15), ZFRPGR2(ex1-17)) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 71 publications
2
58
0
Order By: Relevance
“…77 The rpgr zebrafish morphant presents with a similar retinal phenotype as a consequence of cell death in the dysplastic retina. 78 These zebrafish morphant phenotypes can be rescued by injection of human RP2 or RPGR mRNA, respectively, indicative of a functional role for RP2 and RPGR in the pathogenesis of human X-linked RP. 78 Mutations in the Rhodopsin (RHO) gene are the most common cause of human autosomal dominant RP.…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…77 The rpgr zebrafish morphant presents with a similar retinal phenotype as a consequence of cell death in the dysplastic retina. 78 These zebrafish morphant phenotypes can be rescued by injection of human RP2 or RPGR mRNA, respectively, indicative of a functional role for RP2 and RPGR in the pathogenesis of human X-linked RP. 78 Mutations in the Rhodopsin (RHO) gene are the most common cause of human autosomal dominant RP.…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
“…78 These zebrafish morphant phenotypes can be rescued by injection of human RP2 or RPGR mRNA, respectively, indicative of a functional role for RP2 and RPGR in the pathogenesis of human X-linked RP. 78 Mutations in the Rhodopsin (RHO) gene are the most common cause of human autosomal dominant RP. Rhodopsin is a member of the G-protein-coupled receptor family and has a role in phototransduction in rod photoreceptors.…”
Section: Retinitis Pigmentosamentioning
confidence: 99%
“…Whole 120 hpf larvae were first fixed in 4% paraformaldehyde and permeabilized in proteinase K at room temperature. After blocked in 2% goat serum, the larvae were then incubated in diluted mouse primary antibody raised to rhodopsin (1:1000), which has been verified reactive with zebrafish rhodopsin (Shu et al, 2010). This incubation was performed for 20 h at room temperature with gentle rotation.…”
Section: Rhodopsin Whole Mount Immunostaining and Western Blottingmentioning
confidence: 99%
“…This antibody is commercially available (ab5417; Abcam, Cambridge, UK; R5403; Sigma-Aldrich, St. Louis, MO; sc-57,432; SCBT, Santa Cruz, CA; MAB5356; Millipore, Billerica, MA) and according to the supplier is used to detect rhodopsin also in zebrafish. Accordingly, two recent zebrafish publications used the 1D4 antibody as a marker to examine rhodopsin localization and to describe rod deformations in studies characterizing two RP related genes, RPGR 17 and ZNF513. 18 In our study, we used histologic analysis of a rod-specific transgenic reporter line and surprisingly found that 1D4 does not stain rod outer segments in zebrafish.…”
Section: Resultsmentioning
confidence: 99%